Metabolic resistance to pyrethroids with possible involvement of non-coding ribonucleic acids in Anopheles funestus, the major malaria vector in western Kenya - Isaiah Debrah; Daibin Zhong; Maxwell G. Machani; Godfrey Nattoh; Kevin O. Ochwedo; Collins M. Morang’a; Ming-Chieh Lee; Linda E. Amoah; Andrew K. Githeko; Yaw A. Afrane; Guiyun Yan (BMC Genomics)
Abstract Background The resurgence of Anopheles funestus, a dominant vector of human malaria in western Kenya was partly attributed to insecticide resistance. However, evidence on the molecular basis of pyrethroid resistance in western Kenya is limited. Here, we reported metabolic resistance mechanisms and demonstrated that multiple non-coding Ribonucleic Acids (ncRNAs) could play a potential role in An. funestus resistance to pyrethroid in western Kenya. Anopheles funestus mosquitoes were sampled using aspiration methods in Bungoma, Teso, Siaya, Port Victoria and Kombewa in western Kenya. The F1 progenies were exposed to deltamethrin (0.05%), permethrin (0.75%), DDT (4%) and pirimiphos-methyl (0.25%) following WHO test guidelines. A synergist assay using piperonyl butoxide (PBO) (4%) was conducted to determine cytochrome P450s’ role in pyrethroid resistance. RNA-seq was conducted on a combined pool of specimens that were resistant and unexposed, and the results were compared with those of the FANG susceptible reference strain. This approach aimed to uncover the molecular mechanisms underlying the observed phenotypic pyrethroid resistance. Results Pyrethroid resistance was observed in all sites with an average mortality rate (MR) of 57.6%. Port Victoria had the highest level of pyrethroid resistance to permethrin (MR = 53%) and deltamethrin (MR = 11%. Teso had the lowest level of resistance to permethrin (MR = 70%) and deltamethrin (MR = 87%). Resistance to DDT was observed only in Kombewa (MR = 89%) and Port Victoria (MR = 85%). A full susceptibility to P-methyl (0.25%) was observed in all sites. PBO synergist assay revealed high susceptibility (> 98%) to pyrethroids in all the sites except for Port Victoria (MR = 96%). Whole transcriptomic analysis showed that most gene families associated with pyrethroid resistance comprised non-coding RNAs (67%), followed by immunity proteins (10%), cytochrome P450s (6%), cuticular proteins (5%), olfactory proteins (4%), glutathione S-transferases (3%), UDP-glycosyltransferases (2%), ATP-binding cassettes (2%) and carboxylesterases (1%). Conclusion This study unveils the molecular basis of insecticide resistance in An. funestus in western Kenya, highlighting for the first time the potential role of non-coding RNAs alongside metabolic detoxification in pyrethroid resistance. Targeting non-coding RNAs for intervention development could help in insecticide resistance management.